Pekalongan Sebagai Kota Batik 1950-2007 - Chusnul Hayati (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2012)
The purpose of this paper will explain how Pekalongan City is known as “batik city” and batik as local genius or cultural identity in Pekalongan. Batik in Pekalongan City is not only as economic and cultural asset, but also is as a way of life. Batik society in Pekalongan has sense of belonging and sense of pride towards batik as a beautiful work of art. So, they have sense of obligation to revival and to develop batik. Batik society in Pekalongan is facing the rise and fall of the tides because of there were some kinds economic and political crisis and change. Pekalongan batik is big because of challenge not just the contribution. The golden age of Pekalongan batik was in 1950s--in the end of 1960s, because batik as the important of livelihood in Pekalongan City. Some kinds of crisis and challenge could be the positive impact for it. The reaction of these challenges are appearing the creation and innovation so the new products are born in order to enrich Pekalongan batik. Crisis in 1970s was caused by batik printing technique that changed into silk handmade. The economic crisis in 1997 created batik that used pineapple tight, banana tight, and local silk. As a batik city, Pekalongan is the place where batik strongly influenced by China, Arabic, European-Dutch, and Japanese culture. On the other hand, Pekalongan batik is influenced by local style from Surakarta, Yogyakarta, and other places. These various influences effected Pekalongan batik so beautiful and interesting, have various motif and colorful. To make to be strong as “batik city”, the Government of Pekalongan City defined a slogan: BATIK that means Bersih (clean), Aman (safety), Tertib (disciplinary), Indah (beautiful), and Komunikatif (communicative).Keywords: batik, economy, innovation, cultural identity.